Intravitreal bevacizumab monotherapy in myopic choroidal neovascularisation: 5-year outcomes for the PAN-American Collaborative Retina Study Group. Issue 4 (16th August 2017) - Chhablani, Jay; Paulose, Remya Mareen; Lasave, Andres F; Wu, Lihteh; Carpentier, Cristian; Maia, Mauricio; Lujan, Silvio; Rojas, Sergio; Serrano, Martin; Berrocal, Maria H; Arevalo, J Fernando
Abstract : Purpose: To report the long-term anatomical and visual outcomes of intravitreal bevacizumab (IVB) monotherapy in naive choroidal neovascularisation (CNV) caused by myopia. Methods: Retrospective analysis of naive CNV secondary to myopia that underwent antivascular endothelial growth factor monotherapy was performed. Collected data included demographic details, clinical examination details including visual acuity at presentation and follow-up with imaging and treatment details. Main outcome measures were resolution of CNV activity at the last visit. Secondary outcomes included change in visual acuity, number of injections and adverse events. Results: Thirty-three eyes of 31 subjects with a mean age of 51.48±16.4 years were included. The mean follow-up was 66.47 months. 27 eyes had type 2 CNV and the rest seven eyes had type 1 CNV. The mean number of IVB injections per eye was 4.9. Mean visual acuity at baseline reduced from 0.65±0.33 logMAR units (Snellen equivalent=20/89) to 0.73±0.50 logMAR units (20/107) at final follow-up (p=0.003). The mean central macular thickness decreased from 309.31±86 µm at baseline to 267.5±70.89 µm at the last visit (p=0.03). However, visual acuity was maintained (±1 line of baseline) in 13 eyes (39.4%), ≥2 line improvement in nine (27.3%) eyes and more than two lines worsening in 11 eyes (33.3%). Foveal atrophy was observed at baseline and last visit in 6 (12.5%) and 14 (29.1%), respectively (p=0.007). No systemic adverse events were observed. Conclusion: IVB monotherapy is safe and effective for long-term treatment of CNV secondary to myopia in real life.